Financing Public Elementary and Secondary Education in New York State - Scott R. Sweetland; Stephen L. Jacobson (Educational Considerations, 1998)
The figures suggest that educational expenditures in New York State are not equalized on a per pupil basis and that the goal of providing equal opportunities for education, in terms of equal expenditures on education, is not even close to being achieved.